2016
DOI: 10.1103/physreva.93.010301
|View full text |Cite
|
Sign up to set email alerts
|

Experimental single-photon exchange along a space link of 7000 km

Abstract: Extending the single photon transmission distance is a basic requirement for the implementation of quantum communication on a global scale. In this work we report the single photon exchange from a medium Earth orbit satellite (MEO) at more than 7000 km of slant distance to the ground station at the Matera Laser Ranging Observatory. The single photon transmitter was realized by exploiting the corner cube retro-reflectors mounted on the LAGEOS-2 satellite. Long duration of data collection is possible with such a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 32 publications
2
74
0
Order By: Relevance
“…to-noise ratio and detection rate. Our work extends the limit of long-distance free-space single-photon exchange, which was demonstrated so far with a channel length of about 7000 km by exploiting a Medium-Earth-Orbit (MEO) satellite [27].…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…to-noise ratio and detection rate. Our work extends the limit of long-distance free-space single-photon exchange, which was demonstrated so far with a channel length of about 7000 km by exploiting a Medium-Earth-Orbit (MEO) satellite [27].…”
Section: Introductionsupporting
confidence: 60%
“…where A CCR and A tel are the areas of the CCR and the ground telescope, respectively [31]. An alternative approach is given in [27] in which the FFDP is approximated as a top-hat pattern with solid angle Ω, so that the diffraction transmittance is evaluated as A tel /(ΩR 2 ). Since the solid angle can be estimated by the array cross-section Σ [28,33], we have that…”
Section: Model Of the Channel Lossesmentioning
confidence: 99%
“…Such simplicity renders our source suitable for CubeSat missions, where a small footprint and low energy consumption are of critical importance [20]. Furthermore, the temporal stability of the source attests the compatibility with QKD links with satellites even in Middle Earth Orbit [21], or part of a Global Navigation Satellite Systems [22], where visibility times between the ground station and satellite can exceed the hour.…”
Section: Discussionmentioning
confidence: 98%
“…The distribution of quantum states between distant parties, connected by a free-space link, is one of the main technological challenges towards a global-scale quantum Internet. Several proof-of-concept studies have already demonstrated the high-fidelity transmission of entangled photons up to 143 km for a ground link [144], 1200 km with a satellite link for quantum communication on a global scale [145], and transmission of attenuate laser up to Global Navigation Satellite Orbit [146,147]. However, until very recently, most of the demonstrations used a bipartite binary photonic system while only a few took advantage of qudit encoding.…”
Section: Free-space Linksmentioning
confidence: 99%